Doubleborn : a Dragonborn novel - Forward, Toby, 1950- (Forward, Toby, 1950- Dragonborn., 2015)
Falsely accused of bullying, wizard apprentice Tamrin leaves Canterstock College for Wizards and sets out in search of Sam, the only person to whom she has ever felt a connection, but Sam, adrift since his master Flaxfield died, has been targeted by Flaxfield's old enemy, the powerful wizard Ash.